Hepatic encephalopathy expands the predictivity of model for end‐stage liver disease in liver transplant setting: Evidence by means of 2 independent cohorts. Issue 10 (October 2016) - Lucidi, Cristina; Ginanni Corradini, Stefano; Abraldes, Juan G.; Merli, Manuela; Tandon, Puneeta; Ferri, Flaminia; Parlati, Lucia; Lattanzi, Barbara; Poli, Edoardo; Di Gregorio, Vincenza; Farcomeni, Alessio; Riggio, Oliviero
Abstract : Despite its documented prognostic relevance, hepatic encephalopathy (HE) is not considered in liver transplantation (LT) due to its possible poor objectivity. To override this problem, we aimed to analyze if an objective diagnosis of HE may confer additional mortality risk beyond MELD. Study and validation cohorts of patients with cirrhosis were considered in Italy and Canada, respectively. Patients were considered to be HE+ if an episode of overt HE was documented in a hospitalization. Of the 486 patients enrolled in Italy, 184 (38%) were HE+. During the 6‐month follow‐up, 77 patients died and 50 underwent transplantation. The 6‐month mortality of HE+ versus HE– patients was significantly higher ( P  < 0.001). Model for End‐Stage Liver Disease (MELD; subdistribution hazard ratio [sHR], 1.2; 95% confidence interval [CI], 1.1‐1.2; P  < 0.001), HE+ (sHR, 3.6; 95% CI, 1.8‐7.1; P  < 0.001), and sodium (sHR, 0.9; 95% CI, 0.8‐0.9; P  < 0.001) were independent predictors of 6‐month mortality. In HE+ patients, short‐term mortality increased across the entire MELD spectrum (range, 6‐40). The results were unchanged by including or excluding patients with hepatocellular carcinoma or stratifying patients according to HE characteristics. The higher 6‐month mortality of HE+ versus HE– patients was confirmed also in the Canadian cohort ( P  < 0.001; n = 300, 33% HE+; 33 died, 104 transplanted). A similar and statistically significant C‐index increase derived by the incorporation of HE in MELD was observed both in the Italian (from 0.67 to 0.75) and Canadian (from 0.69 to 0.74) cohorts. A score based on MELD plus 7 points (95% CI, 4‐10) for HE+ patients optimally predicted 6‐month mortality in the 2 cohorts. According to the net reclassification index, by not considering HE, 29% of overall patients were misclassified by MELD score. In conclusion, the incorporation of HE in MELD score might improve the listing and allocation policy in LT. Liver Transplantation 22 1333–1342 2016 AASLD .